Licania arborea fraction bioactive potential assessment in jurkat and cho-k1 cell lines (2016)
ABSTRACT: Introduction: Several species of Chrysobalanaceae plants have shown a variety of biological activities, exhibiting a source of interesting compounds from the pharmacological point of view. Objective: To assess the bioactive potential of L. arborea fractions on Jurkat and CHO-K1 cell lines. Methods: All the experiments were carried out in Jurkat and CHO-K1 (mammalian cell lines). Cytotoxicity of the fractions was assessed via tTrypan blue dye and tetrazolium salt (MTT) assays. Genotoxicity was evaluated determining the sister chromatid exchange (SCE). Antiproliferative effect was estimated by clonogenic assay and cell cycle progression. Furthermore, proliferative kinetics were assessed by SCE of L. arborea fractions. Results: The IC50 of F8 and F10 fractions was approximately 100 µg/mL for Jurkat and CHO-K1 cell lines. Cytotoxicity of the evaluated fractions led to reduced cell viability and cloning capability. Particularly, fraction F8 showed genotoxic effect reflected in increments of SCEs frequency, mainly on Jurkat cells. Conclusions: Jurkat and CHO-K1 cells clearly displayed a dose dependent cytotoxicity and genotoxicity, although the effect was more severe on the lymphoid cell line compared with the noncancerous cells, showing total absence of mitosis in the Jurkat cell line treated with fraction F8 (100μg/mL).